2012
DOI: 10.4168/aair.2012.4.4.214
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Mycobacterial Secretory Proteins Against Established Asthma in BALB/c Mice

Abstract: Purpose Live/killed mycobacteria and culture supernatants can suppress asthmatic reactions. This study investigated whether mycobacterial secretory proteins have therapeutic effects on asthma. Methods Mycobacterium bovis bacille Calmette-Guérin (BCG; 2×10 5 CFUs) and mycobacterial secretory proteins (Ag85 complex, 38-kDa protein or MPB70; 4 or 20 µg) were administered intraperitoneally to female BALB/c mice with established airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…Immunotherapy based on immune deviation is an effective strategy to treat or prevent allergic asthma. Live and dead bacteria, parasite, or bacterial components such as purified protein derivative from Mycobacterium tuberculosis have shown potential to protect mice from developing allergic Th2 responses by inducing Th1 responses . Different intracellular bacterial infections, such as BCG vaccine, can induce strong Th1 immune response, thus suppressing asthmatic reactions by balancing Th1/Th2 responses .…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy based on immune deviation is an effective strategy to treat or prevent allergic asthma. Live and dead bacteria, parasite, or bacterial components such as purified protein derivative from Mycobacterium tuberculosis have shown potential to protect mice from developing allergic Th2 responses by inducing Th1 responses . Different intracellular bacterial infections, such as BCG vaccine, can induce strong Th1 immune response, thus suppressing asthmatic reactions by balancing Th1/Th2 responses .…”
Section: Introductionmentioning
confidence: 99%
“…Native MPB70 protein was purified from M. bovis strain BCG (Bacillus Calmette-Guérin; Tokyo strain) culture filtrate proteins (CFPs) using a 2-step biochemical method as previously described. 9,17 Briefly, M. bovis BCG was grown at 37°C as a surface pellicle on Sauton medium for 6 weeks, after which the CFPs were filter sterilized with a 0.2-μm membrane. The 50-80% ammonium sulfate precipitate (ASP) of the CFPs was dialyzed against 1 mM potassium phosphate buffer (PPB, pH 7.0), loaded onto a hydroxyapatite column equilibrated with 1 mM PPB, and eluted with 1 mM PPB because MPB70 was not retained on the column.…”
Section: Antigen Preparationmentioning
confidence: 99%
“…To determine if individual secreted proteins of M. tuberculosis can modulate asthma, studies have been conducted with single proteins purified from the culture supernatants of M. tuberculosis , i.e., Ag85 complex, 38 kDa protein, and MPB70 [72], and the recombinant Ag85B produced in Escherichia coli [73]. These secreted proteins have been shown to be the inducers of Th1 cytokine IFN-γ from human peripheral blood cells [74].…”
Section: Introductionmentioning
confidence: 99%
“…These secreted proteins have been shown to be the inducers of Th1 cytokine IFN-γ from human peripheral blood cells [74]. The findings in the experimental asthma model showed that immunization of mice with the purified and recombinant proteins provided protection against asthma in the ovalbumin-challenge model [72, 73]. With respect to cells and cytokines, mice immunized with individual mycobacterial proteins preferentially activated Th1 cells and showed increased IFN-γ/IL-5 ratios [72, 73].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation